Cyclic peptide natural products chart the frontier of oral bioavailability in the pursuit of undruggable targets. (June 2017) - Naylor, Matthew R; Bockus, Andrew T; Blanco, Maria-Jesus; Lokey, R Scott
Highlights: The pursuit of 'undruggable' therapeutic targets has reinvigorated interest in natural products. Peptides have been traditionally considered poor pharmaceutical candidates. Some large cyclic peptide natural products have proven bioactivity and oral bioavailability. Cyclic peptides have been synthesized to explore ADME optimization. New and optimized chemical structures are shown to achieve unprecedented oral bioavailability. Abstract : As interest in protein–protein interactions and other previously-undruggable targets increases, medicinal chemists are returning to natural products for design inspiration toward molecules that transcend the paradigm of small molecule drugs. These compounds, especially peptides, often have poor ADME properties and thus require a more nuanced understanding of structure-property relationships to achieve desirable oral bioavailability. Although there have been few clinical successes in this chemical space to date, recent work has identified opportunities to introduce favorable physicochemical properties to peptidic macrocycles that maintain activity and oral bioavailability.